2019
DOI: 10.1002/jmri.26970
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Efficacy of Contrast‐Enhanced MRI in Detecting Residual or Recurrent Hepatocellular Carcinoma After Transarterial Chemoembolization: A Systematic Review and Meta‐analysis

Abstract: Background The diagnostic efficacy of contrast‐enhanced magnetic resonance imaging (CEMRI) in diagnosing residual or recurrent hepatocellular carcinoma (HCC) after transarterial chemoembolization (TACE) is currently not completely clear. Purpose To investigate the diagnostic efficacy of CEMRI in detecting residual or recurrent HCCs after TACE by meta‐analysis. Study Type Systematic review and meta‐analysis. Population A systematic literature search was performed in PubMed, Embase, Web of Science, Ovid, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…The diagnostic values of CEMRI and CECT for detecting HCC after TACE have already been illustrated in previous studies 40 41. A meta-analysis by Zhong et al included 11 studies comparing the diagnostic value of contrast-enhanced ultrasonography (CEUS) and CECT for detecting HCC after TACE.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…The diagnostic values of CEMRI and CECT for detecting HCC after TACE have already been illustrated in previous studies 40 41. A meta-analysis by Zhong et al included 11 studies comparing the diagnostic value of contrast-enhanced ultrasonography (CEUS) and CECT for detecting HCC after TACE.…”
Section: Discussionmentioning
confidence: 96%
“…They pointed out that the sensitivity (CEUS, 0.97; CECT, 0.72) and negative predictive value (CEUS, 0.90; CECT, 0.51) of CEUS were better than those of CECT, while the specificity (CEUS, 0.86; CECT, 0.99) of CECT was higher than that of CEUS 40. Moreover, Liu et al conducted a meta-analysis of 13 studies and found that CEMRI had a relatively high diagnostic value (sensitivity: 91%; specificity: 93%; PLR: 12.22; NLR: 0.09; DOR: 126.99; AUC: 0.97) for diagnosing HCC after TACE and hence could be regarded as an alternative diagnostic method 41. However, one of the above studies reported on the diagnostic performance of CECT and CEUS, while the other reported that of CEMRI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MRI has emerged as the most accurate and acceptable tool for longitudinal follow‐up after TACE, although the accuracy in this high‐risk population is not well known. In this issue of JMRI, a systematic review presented by Liu et al titled "Diagnostic efficacy of contrast‐enhanced MRI in detecting residual or recurrent hepatocellular carcinoma after transarterial chemoembolization: A systematic review and meta‐analysis" provides insight into the potential of MRI for this purpose.…”
mentioning
confidence: 99%